Cerium-based rare earth modified UHMWPE fiber, and preparation method and application thereof
Patent Information
- Application Number
- CN202611211894.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-08-11
AI Technical Summary
[0006]常规引入的聚合物接枝层(如聚丙烯酸)在遭遇混凝土孔隙液的强碱性(pH>12.5)环境时,极易发生溶胀脱落;若试图向接枝层中引入常规金属交联剂,这些活性离子在水泥水化初期的复杂离子竞争环境中会迅速析出并生成无活性的沉淀物(如硫酸盐),不仅彻底丧失了界面催化与桥接活性,更无法与基体中的C-S-H凝胶(水化硅酸钙凝胶)形成稳定的化学键合,最终导致纤维与基体在长期服役过程中的脱粘与界面滑移拔出破坏
[0027]有益效果:本发明利用稀土光敏引发特性实现温和接枝,在不损伤纤维本体强度的前提下实现表面活化;通过独特的碱激发预矿化工艺有效避免了稀土离子在水泥高碱环境中的失活,原始UHMWPE纤维本身表面惰性、疏水,在水泥浆体中极易浮于浆体表面、发生纤维团聚、结团,分散性很差,接枝层转化为羧酸盐后带来适度亲水性,改善UHMWPE纤维与水相水泥浆的浸润能力,有利于纤维在拌合阶段均匀分散,减少纤维浮聚、抱团,构建出“纤维-聚合物-Ce-O-Ca”多级界面结构,提升了水工混凝土的抗拉、抗冲击耗能及抗渗透性能。
Smart Images

Figure CN122707381B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to cement-based composite materials, and more particularly to a cerium-based rare earth modified UHMWPE fiber and its preparation method. Background Technology
[0002] Cement-based composite materials are widely used in hydraulic structures, bridges, and tunnels due to their high compressive strength, convenient casting, and good economy. However, cement-based materials themselves have typical brittle characteristics, low tensile strength, and are prone to microcracks. Under the scouring and abrasion of high-speed sand-laden water flows and frequent impacts from external loads such as passing ships, hydraulic concrete is highly susceptible to wear, erosion, and spalling. To improve the toughness and impact resistance of hydraulic concrete, fiber reinforcement materials are usually incorporated into the system. Ultra-high molecular weight polyethylene (UHMWPE) fibers, with their extremely high elastic modulus, excellent tensile strength, and outstanding corrosion resistance, perfectly meet the stringent requirements of the hydraulic environment for materials to be rust-free and highly durable, making them an ideal choice for toughening hydraulic concrete.
[0003] In existing research and engineering practice, due to the highly symmetrical molecular chains of UHMWPE fibers and the lack of polar groups, their surface exhibits extremely strong chemical inertness and hydrophobicity, resulting in very poor interfacial compatibility with inorganic silicate cement matrices. To overcome this deficiency, commonly used fiber surface modification methods mainly include chemical etching with strong oxidants (such as chromic acid, potassium permanganate, and concentrated sulfuric acid), ozone oxidation, and plasma treatment, aiming to introduce polar groups such as hydroxyl and carboxyl groups by disrupting the fiber surface structure to improve hydrophilicity. Furthermore, in the field of advanced ceramics and other inorganic non-metallic materials, rare earth compounds (such as cerium series elements) are often used as lattice strengthening and interfacial toughening agents; however, due to their high cost, they are rarely directly incorporated into cement-based systems in large quantities.
[0004] Although the above-mentioned traditional modification schemes can improve the hydrophilicity of fibers to some extent, the existing technology still faces the following deep-seated structural problems when dealing with complex high-alkalinity concrete environments: First, it faces the irreconcilable contradiction between fiber "surface activation" and "bulk strength retention".
[0005] Traditional strong oxidation etching inevitably leads to deep breakage of the polymer backbone, causing severe surface stress concentration, which in turn significantly weakens the high-strength bulk mechanical properties upon which UHMWPE fibers depend. Secondly, it faces the problem of interfacial failure and structural collapse of polar graft layers in a strongly alkaline environment.
[0006] Conventionally introduced polymer grafting layers (such as polyacrylic acid) are prone to swelling and detachment when exposed to the highly alkaline environment (pH>12.5) of concrete pore fluid. If conventional metal crosslinking agents are introduced into the grafting layer, these active ions will quickly precipitate and generate inactive precipitates (such as sulfates) in the complex ion competition environment during the early stage of cement hydration. This not only completely loses the interfacial catalytic and bridging activity, but also fails to form stable chemical bonds with the CSH gel (hydrated calcium silicate gel) in the matrix, ultimately leading to debonding and interfacial slippage and pull-out damage between the fiber and the matrix during long-term service. Summary of the Invention
[0007] Objective of the invention: To provide a cerium-based rare earth modified UHMWPE fiber, its preparation method, and its application, in order to solve the above-mentioned problems in the prior art.
[0008] Technical solution: A cerium-based rare earth modified UHMWPE fiber, comprising a UHMWPE fiber matrix and a polymer layer grafted onto the surface of the UHMWPE fiber matrix, wherein cerium ions or cerium hydroxide particles coordinated with the polymer layer are distributed in the polymer layer.
[0009] Preferred materials include cerium hydroxide nanoparticles and residual cerium ions, such as cerium hydroxide.
[0010] The cerium-based rare earth modified UHMWPE fiber is prepared by a method including the following steps:
[0011] In the presence of an initiator, unsaturated monomers are photo-initiated grafted onto the surface of the UHMWPE fiber matrix to form the polymer layer; wherein the initiator is a cerium salt containing tetravalent cerium ions, and the unsaturated monomer is a carboxyl-containing unsaturated monomer;
[0012] The fibers that have undergone photoinitiated graft polymerization are immersed in an alkaline calcium-containing solution for in-situ mineralization.
[0013] In one embodiment, it includes cerium ammonium nitrate, cerium sulfate, and cerium fluoride. More preferably, it includes at least one of cerium ammonium nitrate and cerium sulfate.
[0014] In one embodiment, the UHMWPE fibers have an average diameter of 20 μm and a density of 0.97 g / cm³. 3 .
[0015] According to another aspect of this application, a method for preparing cerium-based rare earth modified UHMWPE fibers is also provided, characterized by comprising the following steps:
[0016] Step 1: The UHMWPE fiber matrix is placed in a coating solution containing an initiator and an unsaturated monomer and subjected to ultraviolet irradiation, so that the unsaturated monomer is grafted and polymerized on the surface of the UHMWPE fiber matrix to form the polymer layer; wherein, the initiator is a cerium salt containing tetravalent cerium ions, and the unsaturated monomer is an unsaturated monomer containing carboxyl groups; preferably, by weight, 10 parts of the UHMWPE fiber matrix are fully expanded and placed in 80-100 parts of a coating solution containing an initiator and an unsaturated monomer for ultraviolet irradiation;
[0017] Step 2: The fibers treated in Step 1 are immersed in an alkaline calcium-containing solution for in-situ mineralization, which converts cerium ions in the polymer layer into nanoparticles.
[0018] In one embodiment, the coating liquid comprises, by weight percentage: 0.5 wt% to 2.0 wt% cerium ammonium nitrate, 5 wt% to 10 wt% acrylic acid, and the balance being deionized water.
[0019] In one embodiment, the wavelength of the ultraviolet irradiation is 365 nm, and the irradiation power is 80 mW / cm². 2 Up to 100mW / cm 2 Preferably, the irradiation time is 15-25 minutes, more preferably 18 to 22 minutes, and even more preferably 20 minutes.
[0020] In one embodiment, the ultraviolet irradiation is carried out under nitrogen protection, and the oxygen concentration in the operating environment is less than 0.1%.
[0021] In one embodiment, the alkaline calcium-containing solution is a saturated calcium hydroxide solution with a pH value greater than or equal to 12.6. For example, a saturated calcium hydroxide solution at room temperature (20-25°C).
[0022] In one embodiment, the nanoparticles are cerium hydroxide particles with a size of 2 nm to 10 nm.
[0023] In one embodiment, a pre-wetting treatment step is included before step one: the UHMWPE fiber matrix is immersed in anhydrous ethanol for ultrasonic treatment.
[0024] Preferably, the UHMWPE fiber is immersed in anhydrous ethanol and ultrasonically treated with parameters of 200W, 40kHz, and 5 minutes, and then drained until the ethanol residue is <2%vol.
[0025] In one embodiment, step two is followed by a post-processing step: rinsing the treated fibers with deionized water and then drying them at 60°C.
[0026] According to another aspect of this application, the application of the cerium-based rare earth modified UHMWPE fiber in the preparation of cement-based composite materials or hydraulic concrete is also provided.
[0027] Beneficial effects: This invention utilizes the photosensitive initiation characteristics of rare earth elements to achieve gentle grafting, realizing surface activation without damaging the strength of the fiber itself; through a unique alkali-activated pre-mineralization process, it effectively avoids the deactivation of rare earth ions in the high-alkali environment of cement. The original UHMWPE fiber itself is inert and hydrophobic, and it is very easy to float on the surface of cement paste, resulting in fiber agglomeration and clumping, with very poor dispersibility. After the grafted layer is converted into carboxylate, it brings moderate hydrophilicity, improving the wetting ability of UHMWPE fiber with aqueous cement paste, which is conducive to the uniform dispersion of fiber during the mixing stage, reducing fiber agglomeration and clumping, and constructing a multi-level interface structure of "fiber-polymer-Ce-O-Ca", which improves the tensile strength, impact resistance, energy dissipation resistance and impermeability of hydraulic concrete. Attached Figure Description
[0028] Figure 1 This is a SEM image of the UHMWPE fiber before modification in this application.
[0029] Figure 2 This is a SEM image of the modified UHMWPE fiber in this application.
[0030] Figure 3 This is a magnified view of the surface particles after the UHMWPE fiber modification in this application.
[0031] Figure 4 This is an XPS result diagram of UHMWPE fiber in this application. Detailed Implementation
[0032] Example 1: Contains a UHMWPE fiber matrix. The UHMWPE fiber is a commercially available product with a density of 0.97 g / cm³. 3 The coating solution is supplied by Dongguan Suowete Special Wire & Tape Co., Ltd. The initiator is a cerium salt containing tetravalent cerium ions, specifically cerium ammonium nitrate, with a mass percentage of 1.2 wt% in the coating solution; the unsaturated monomer is a carboxyl-containing unsaturated monomer, specifically acrylic acid, with a mass percentage of 7.5 wt% in the coating solution, and the balance of the coating solution is deionized water. The acrylic acid is supplied by Shandong Tengbo Chemical Technology Co., Ltd.
[0033] This application does not simply coat the fiber surface with a layer of polyacrylic acid, but rather constructs a composite interface structure of "UHMWPE matrix - covalently grafted PAA chain - nano Ce(OH)3 particles", which can suppress the risk of excessive swelling and hydrolysis of the grafted layer when exposed to water. The mechanism is twofold:
[0034] The grafted chains are covalently grafted onto the surface of UHMWPE fibers, not as a physical coating; even if the carboxyl groups are converted into carboxylates, the polymer chain backbone is covalently anchored to the fiber matrix and will not dissolve and detach from the fiber as a whole.
[0035] Nano-Ce(OH)3 generated in situ within the grafting network can react with the -COO group of polyacrylic acid. - Coordination crosslinking occurs, which plays an ionic crosslinking role in the polymer graft network, partially offsetting the water absorption and swelling caused by carboxylate, and limiting the excessive swelling of the polymer graft layer in an aqueous environment; at the same time, the nano Ce-O sites can form chemical bonds with cement hydration CSH gel, the graft layer bonds outward with hydration products, and covalently binds fibers inward, forming a stable multi-level interface.
[0036] like Figures 1-4 The image shows the SEM and XPS comparison results of UHMWPE fibers before and after modification, to confirm the successful grafting of acrylic acid and the effective immobilization of the cerium component in the present invention.
[0037] Comparison of SEM morphology before and after modification reveals that the fiber surface is smooth before modification, while a uniform functional coating layer is formed on the fiber surface after modification, with 2-10nm nanoparticles dispersedly distributed.
[0038] Comparing the XPS results, it can be found that the PE fiber before modification only showed a strong C1s peak and a very weak oxygen pollution signal. After modification, in addition to the main C1s peak, obvious O1s characteristic peaks and Ce3d characteristic peaks were also observed, which indicates that Ce element is chemically bonded to the fiber surface.
[0039] Step 1: Immerse the UHMWPE fiber matrix in anhydrous ethanol for ultrasonic treatment to achieve pre-wetting.
[0040] Step two involves placing the pre-wetted UHMWPE fiber matrix into a coating solution containing the aforementioned initiator and unsaturated monomers for ultraviolet (UV) irradiation. This allows the unsaturated monomers to undergo photo-initiated graft polymerization on the surface of the UHMWPE fiber matrix, forming a polymer layer. The UV irradiation is performed under nitrogen protection, with an oxygen concentration of less than 0.1% in the operating environment. The UV irradiation time is 20 minutes, the wavelength is 365 nm, and the irradiation power is 90 mW / cm². 2 .
[0041] Step 3: The fiber that has completed photo-initiated graft polymerization is immersed in an alkaline calcium-containing solution for in-situ mineralization treatment. The alkaline calcium-containing solution is a saturated calcium hydroxide solution with a pH value of 12.6, which converts cerium ions in the polymer layer into nanoparticles.
[0042] Specifically, the alkaline-activated in-situ mineralization step of the present invention is as follows: the modified grafted fiber is immersed in a saturated Ca(OH)2 solution (pH=12.6) for 1 hour to achieve mineralization. The system is not a free cerium ammonium nitrate salt directly added to a strong alkaline solution. The cerium ions are not free ions, but are pre-complexed and anchored by the carboxyl groups of the covalently grafted polyacrylic acid chain.
[0043] Chemical reaction process: After grafting initiated by ultraviolet light, polyacrylic acid chains are grafted onto the fiber surface, Ce 4+ Ce is generated during the ultraviolet process. 3+ Ce 3+ It forms a coordination complex with the -COOH group on the grafted chain and is fixed inside the polymer grafting network, rather than being a free Ce in the liquid phase. 3+ .
[0044] When immersed in a saturated Ca(OH)₂ strong base system: -COO-Ce 3+ +OH-→-COO-+Ce(OH)3 (nano-suspension);
[0045] The grafted chain spatial grid restricts the growth space of Ce(OH)3 crystal nuclei. The crystal nuclei are confined in the gaps of the grafted chain network, inhibiting excessive growth and aggregation of crystal nuclei, and finally generating 2-10nm nano Ce(OH)3 particles, which are embedded in the grafted polymer network. The steric hindrance of the polymer chain prevents the nanoparticles from agglomerating and settling, so no micron-scale macroscopic precipitates are generated.
[0046] The process conditions of this invention do not preferentially generate CeO2: CeO2 generation requires a strong oxidizing environment, high-temperature calcination, or prolonged air oxidation; this invention uses room-temperature liquid-phase treatment and nitrogen-protected grafting throughout the process, and the alkali-activated mineralization is also done through room-temperature immersion, thus lacking CeO2. 3+ Oxidized to Ce 4+ The conditions for generating CeO2 are then determined, and the main product is nano-cerium hydroxide Ce(OH)3.
[0047] Step four: The treated fibers are rinsed with deionized water and then dried at 60°C to obtain cerium-based rare earth modified UHMWPE fibers. During testing, the modified fibers are added to the reference concrete at a dosage of 0.4 vol%.
[0048] Example 2: The initiator is cerium ammonium nitrate, with a mass percentage of 0.5 wt% in the coating solution; the unsaturated monomer is acrylic acid, with a mass percentage of 5 wt% in the coating solution; the balance of the coating solution is deionized water. The preparation method is the same as in Example 1, except that the ultraviolet irradiation power in step two is 80 mW / cm². 2 .
[0049] Example 3: The initiator is cerium ammonium nitrate, with a mass percentage of 2 wt% in the coating solution; the unsaturated monomer is acrylic acid, with a mass percentage of 10 wt% in the coating solution; the balance of the coating solution is deionized water. The preparation method is the same as in Example 1, except that the ultraviolet irradiation power in step two is 100 mW / cm². 2 .
[0050] Example 4: The initiator is a cerium salt containing tetravalent cerium ions, specifically cerium sulfate, with a mass percentage of 1.2 wt% in the coating solution; the unsaturated monomer is a carboxyl-containing unsaturated monomer, specifically acrylic acid, with a mass percentage of 7.5 wt% in the coating solution; the balance of the coating solution is deionized water. The preparation method is the same as in Example 1.
[0051] Example 5: The initiator is a cerium salt containing tetravalent cerium ions, specifically cerium ammonium nitrate, with a mass percentage of 1.2 wt% in the coating solution; the unsaturated monomer is a carboxyl-containing unsaturated monomer, specifically methacrylic acid, with a mass percentage of 7.5 wt% in the coating solution; the balance of the coating solution is deionized water. The preparation method is the same as in Example 1.
[0052] Example 6: The initiator is cerium ammonium nitrate, with a mass percentage of 0.5 wt% in the coating solution; the unsaturated monomer is acrylic acid, with a mass percentage of 10 wt% in the coating solution; the balance of the coating solution is deionized water. The preparation method is the same as in Example 1. This example is a cross-validation scheme used to verify the effect of extreme cross-combination when the initiator concentration is at the lower limit and the unsaturated monomer concentration is at the upper limit, that is, to verify whether an extremely low concentration of initiator can support the formation of a grafted network with the highest concentration of monomer.
[0053] Example 7: The initiator is cerium ammonium nitrate, with a mass percentage of 2 wt% in the coating solution; the unsaturated monomer is acrylic acid, with a mass percentage of 5 wt% in the coating solution; the balance of the coating solution is deionized water. The preparation method is the same as in Example 1. This example is a cross-validation scheme used to verify the extreme cross-combination effect when the initiator concentration is at its upper limit and the unsaturated monomer concentration is at its lower limit, that is, to verify whether an excess of initiator will cause severe free radical quenching or fiber backbone degradation.
[0054] Example 8: The initiator is cerium ammonium nitrate, with a mass percentage of 1.2 wt% in the coating solution; the unsaturated monomer is acrylic acid, with a mass percentage of 10 wt% in the coating solution; the balance of the coating solution is deionized water. The preparation method is the same as in Example 1, except that the ultraviolet irradiation power in step two is 80 mW / cm². This example is a cross-validation scheme used to verify the extreme cross-combination effect when the monomer concentration is at the upper limit and the ultraviolet irradiation power is at the lower limit, that is, to verify whether the extremely low excitation energy can overcome the reaction activation energy of the high concentration system.
[0055] Comparative Example 1: The initiator was cerium ammonium nitrate, with a mass percentage of 1.2 wt% in the coating solution; the unsaturated monomer was acrylic acid, with a mass percentage of 7.5 wt% in the coating solution; the balance of the coating solution was deionized water. The preparation method was the same as in Example 1, except that the in-situ mineralization treatment in step three was omitted. That is, the fibers that had undergone photoinitiated graft polymerization were directly rinsed with deionized water and then dried at 60°C. Compared with Example 1, this comparative example did not undergo in-situ mineralization treatment involving immersion in an alkaline calcium-containing solution.
[0056] Comparative Example 2: The initiator was benzophenone, with a mass percentage of 1.2 wt% in the coating solution; the unsaturated monomer was acrylic acid, with a mass percentage of 7.5 wt% in the coating solution; the balance of the coating solution was deionized water. The preparation method was the same as in Example 1. Compared with Example 1, this comparative example replaced the initiator with a cerium salt containing tetravalent cerium ions, using a conventional non-rare earth photoinitiator.
[0057] Comparative Example 3: The initiator was cerium ammonium nitrate, with a mass percentage of 1.2 wt% in the coating solution; the unsaturated monomer was acrylic acid, with a mass percentage of 7.5 wt% in the coating solution; the balance of the coating solution was deionized water. The preparation method was the same as in Example 1, except that in step three, the saturated calcium hydroxide solution was replaced with a sodium hydroxide solution with a pH of 12.6. Compared with Example 1, this comparative example used a conventional strong alkaline solution without calcium ions for mineralization treatment.
[0058] Comparative Example 4: The initiator was cerium ammonium nitrate, with a mass percentage of 1.2 wt% in the coating solution; the unsaturated monomer was acrylic acid, with a mass percentage of 7.5 wt% in the coating solution; the balance of the coating solution was deionized water. The preparation method was the same as in Example 1, except that in step two, ultraviolet irradiation was not used; instead, the mixture was soaked in a strong oxidizing solution of potassium permanganate and sulfuric acid for thirty minutes before conventional chemical grafting. Compared with Example 1, this comparative example used a conventional strong oxidizing chemical grafting process instead of the photo-initiated grafting polymerization process.
[0059] Comparative Example 5: The initiator was cerium ammonium nitrate, with a mass percentage of 0.1 wt% in the coating solution; the unsaturated monomer was acrylic acid, with a mass percentage of 2 wt% in the coating solution; the balance of the coating solution was deionized water. The preparation method was the same as in Example 1.
[0060] Comparative Example 6: The initiator was cerium ammonium nitrate, with a mass percentage of 3 wt% in the coating solution; the unsaturated monomer was acrylic acid, with a mass percentage of 15 wt% in the coating solution; the balance of the coating solution was deionized water. The preparation method was the same as in Example 1.
[0061] The cerium-based rare earth modified UHMWPE fibers of Examples 1-8 and Comparative Examples 1-6 were subjected to tensile strength testing and toughening modification performance testing of hydraulic concrete. The results are shown in Table 1.
[0062] Monofilament tensile strength: The dry breaking strength of the fiber was tested according to GB / T14337-2022 "Test Method for Tensile Properties of Chemical Fibers (Short Fibers)". The monofilament breaking strength retention rate was calculated using the following formula:
[0063] δ=(σ x / σ0)×100%;
[0064] Where, σ x σ0 represents the dry fracture strength of the modified UHMWPE, and σ0 represents the dry fracture strength of the unmodified UHMWPE.
[0065] The concrete mix proportion used for the concrete performance test was PO42.5 cement: medium sand: 5~10 crushed stone: 10~20 crushed stone: water = 460:734:330:770:156, with a PE fiber volume content of 0.4%. The 28-day compressive strength, flexural strength, and chloride ion migration coefficient were tested according to DL / T5150-2017 "Test Procedure for Hydraulic Concrete". The impact resistance of the concrete was tested according to CECS13:2009 "Standard Test Method for Fiber Reinforced Concrete", with a drop hammer weight of 4.5 kg and a drop height of 900 mm.
[0066] Table 1. Test Results
[0067]
[0068] Comparing the data from Example 1 and Comparative Example 1 (mineralization step omitted), it is evident that without pre-mineralization treatment with calcium-containing alkali solution, free rare earth ions on the fiber surface will rapidly deactivate due to the highly alkaline and competitive ion environment when directly mixed into concrete. Because a multi-level interface structure of "fiber-polymer-Ce-O-Ca" cannot be formed, the interfacial bonding performance between UHMWPE and the concrete matrix deteriorates. Consequently, the 28-day compressive strength, flexural strength, and impact resistance of the modified concrete decrease, while the chloride ion migration coefficient increases.
[0069] Analysis of the test results from Example 1 and Comparative Example 2 (using common photoinitiators such as benzophenone) shows that while common initiators can achieve grafting, they cannot form an effective Ce-O-Ca complex network on the fiber surface. Due to the deteriorated performance of the fiber-matrix interface transition zone, the 28-day compressive strength, flexural strength, and impact resistance of the modified concrete are all reduced, the chloride ion migration coefficient increases, and the compactness deteriorates.
[0070] Example 1 was compared with Comparative Example 3 (using NaOH solution of the same pH value). Due to the lack of calcium ions, although the pH value was the same, the NaOH system could not form nano-confined multi-level interfacial bonds with the modified rare earth polymer. Therefore, the 28-day compressive strength, flexural strength, and impact resistance of the modified concrete were all reduced, while the chloride ion migration coefficient increased. This, in turn, proves that the in-situ mineralization step of the present invention has a clear structural induction purpose.
[0071] Compared with Comparative Example 1 and Comparative Example 4 (traditional strong acid chemical oxidation grafting), the strong acid treatment conditions resulted in a significant reduction in the bulk mechanical properties of UHMWPE fibers, with the single filament breaking strength retention rate falling below 70%. Due to the reduced fiber breaking strength and the presence of numerous weak points on the fiber surface, the 28-day compressive strength, flexural strength, and impact resistance of the modified concrete were all reduced. The impact resistance of the concrete after initial cracking also decreased significantly (the difference in impact energy consumption between final cracking and initial cracking was small), severely impacting the toughening and modification efficiency of the fibers. Therefore, the UV photo-initiated process of this invention protects the bulk mechanical properties of the fibers while achieving surface activation.
[0072] A comprehensive comparison of Examples 1 to 6 shows that when the grafting rate is below the lower limit, insufficient grafting leads to weak interfacial performance, while when it is above the upper limit, initiator self-polymerization leads to coating embrittlement and peeling.
[0073] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details of the above embodiments. Within the scope of the technical concept of the present invention, various equivalent transformations can be made to the technical solutions of the present invention, and these equivalent transformations all fall within the protection scope of the present invention.
Claims
1. A cerium-based rare earth modified UHMWPE fiber, characterized in that, The invention comprises a UHMWPE fiber matrix and a polymer layer grafted onto the surface of the UHMWPE fiber matrix, wherein cerium ions or cerium hydroxide particles coordinated with the polymer layer are distributed in the polymer layer. The cerium-based rare earth modified UHMWPE fiber is prepared by a method including the following steps: In the presence of an initiator, unsaturated monomers are photo-initiated grafted onto the surface of the UHMWPE fiber matrix to form the polymer layer; wherein the initiator is a cerium salt containing tetravalent cerium ions, and the unsaturated monomer is a carboxyl-containing unsaturated monomer; The fibers that have undergone photoinitiated graft polymerization are immersed in an alkaline calcium-containing solution for in-situ mineralization, which converts cerium ions in the polymer layer into nanoparticles. The alkaline calcium-containing solution is a saturated calcium hydroxide solution; the nanoparticles are cerium hydroxide particles with a size of 2 nm to 10 nm.
2. A method for preparing cerium-based rare earth modified UHMWPE fibers as described in claim 1, characterized in that, Includes the following steps: Step 1: The UHMWPE fiber matrix is placed in a coating liquid containing an initiator and an unsaturated monomer and subjected to ultraviolet irradiation, so that the unsaturated monomer is grafted and polymerized on the surface of the UHMWPE fiber matrix to form the polymer layer; wherein, the initiator is a cerium salt containing tetravalent cerium ions, and the unsaturated monomer is an unsaturated monomer containing carboxyl groups; Step 2: The fibers treated in Step 1 are immersed in an alkaline calcium-containing solution for in-situ mineralization, which converts cerium ions in the polymer layer into nanoparticles.
3. The method according to claim 2, characterized in that, The coating liquid comprises, by mass percentage: 0.5 wt% to 2 wt% cerium ammonium nitrate, 5 wt% to 10 wt% acrylic acid, and the balance being deionized water.
4. The method according to claim 2, characterized in that, The ultraviolet irradiation wavelength is 365 nm, and the irradiation power is 80 mW / cm². 2 Up to 100mW / cm 2 The irradiation time is 15-25 minutes.
5. The method according to claim 2, characterized in that, The ultraviolet irradiation is carried out under nitrogen protection, and the oxygen concentration in the operating environment is less than 0.1%.
6. The method according to claim 2, characterized in that, Before step one, there is also a pre-wetting treatment step: the UHMWPE fiber matrix is immersed in anhydrous ethanol for ultrasonic treatment.
7. The method according to claim 2, characterized in that, Step two is followed by a post-processing step: the treated fibers are rinsed with deionized water and then dried at 60°C.
8. The application of the cerium-based rare earth modified UHMWPE fiber as described in claim 1 in the preparation of cement-based composite materials or hydraulic concrete.
Citation Information
Patent Citations
Modified ultrahigh molecular weight polyethylene fiber and preparation method thereof
CN102505474A
Method for treating surfaces of ultra-high-molecular-weight polyethylene fibers
CN105220503A